A dp53-dependent mechanism involved in coordinating tissue growth in Drosophila. - Duarte Mesquita (Public Library of Science (PLoS), 2010)
Coordination of growth between and within organs contributes to the generation of well-proportioned organs and functionally integrated adults. The mechanisms that help to coordinate the growth between different organs start to be unravelled. However, whether an organ is able to respond in a coordinated manner to local variations in growth caused by developmental or environmental stress and the nature of the underlying molecular mechanisms that contribute to generating well-proportioned adult organs under these circumstances remain largely unknown. By reducing the growth rates of defined territories in the developing wing primordium of Drosophila, we present evidence that the tissue responds as a whole and the adjacent cell populations decrease their growth and proliferation rates. This non-autonomous response occurs independently of where growth is affected, and it is functional all throughout development and contributes to generate well-proportioned adult structures. Strikingly, we underscore a central role of Drosophila p53 (dp53) and the apoptotic machinery in these processes. While activation of dp53 in the growth-depleted territory mediates the non-autonomous regulation of growth and proliferation rates, effector caspases have a unique role, downstream of dp53, in reducing proliferation rates in adjacent cell populations. These new findings indicate the existence of a stress response mechanism involved in the coordination of tissue growth between adjacent cell populations and that tissue size and cell cycle proliferation can be uncoupled and are independently and non-autonomously regulated by dp53.